Method for preventing carbonization of concrete structure and structure thereof
By wrapping the water-absorbable outer leads in the concrete structure, the carbonization-proof liquid is transported to the structure, achieving continuous moisturizing and acid balance, solving the durability problem caused by carbonization of the concrete structure and extending the service life of the structure.
Patent Information
- Application Number
- CN202510015678.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-03-18
AI Technical Summary
The concrete structure causes steel bar corrosion, volume expansion and crack formation due to carbonization, which affects the stability and durability of the structure.
Before pouring concrete, wrap the absorbable outer lead longitudinally or vertically, and use the trajectory of the outer lead to transfer liquids that prevent the concrete from carbonizing (such as a mixed solution of water and citric acid) to the inside of the reinforced concrete structure, achieving continuous moisturizing and internal acid balance.
By reducing the transmission rate of carbon dioxide, the diffusion of CO2 in concrete is suppressed, the degree of carbonization of concrete structures is significantly reduced, and the service life of reinforced concrete structures is extended.
Smart Images

Figure CN119640973A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a method and a structure for preventing carbonization of a concrete structure. Background Art
[0002] Due to the ubiquitous presence of carbon dioxide in nature and the content of alkaline substances in concrete, the carbonization process of concrete is inevitable. Concrete carbonization will affect the stability and durability of concrete structures. In reinforced concrete structures, a passivation film is formed on the surface of the steel bars due to the high alkaline environment, which effectively prevents the steel bars from rusting. However, when concrete is carbonized, its alkalinity decreases, causing the passivation film to be destroyed, thereby causing steel bar corrosion, volume expansion and crack formation, accelerating the transmission of carbon dioxide, and further aggravating steel bar corrosion.
[0003] In order to reduce the adverse effects of carbonization on reinforced concrete structures, coating a layer of organic or inorganic coating on the concrete surface to seal the pores and prevent CO2 from diffusing into the interior is an effective solution. For example, patent CN216787107U discloses an anti-carbonization concrete pipe column, which is equipped with a corrosion-resistant coating to ensure that the device can be used for a long time in an underground environment, thereby reducing the damage to its integrity caused by the external environment, extending the service life of the structure, and effectively preventing carbonization. In addition, patent application CN103333559A discloses a water-based transparent concrete waterproof and anti-carbonization coating, which consists of emulsion, water, transparent powder, highly transparent filler, dust reduction agent, dispersant, wetting agent, defoamer, film-forming aid and thickening and leveling agent, wherein the emulsion is a single-component water-based styrene-methacrylate-acrylate copolymer emulsion, the transparent powder is anhydrous sodium sulfate, the highly transparent filler is white glass powder, the dispersant is sodium polyacrylate, the wetting agent is alkylphenol polyoxyethylene ether, the film-forming aid is 2,2,4-1,3-pentanediol monoisobutyrate, and the thickening and leveling agent is polyurethane. However, this type of organic coating has poor aging resistance, insufficient compatibility with cement inorganic materials, and unsatisfactory anti-carbonization ability.
[0004] Considering the compatibility with cement inorganic materials, inorganic concrete anti-carbonization coatings have been reported. For example, patent CN101693610B discloses a concrete anti-carbonization coating, which is prepared by the following components in parts by weight: 315-525 parts by weight of cement, 45-75 parts by weight of steel slag powder, 45-75 parts by weight of fly ash, 45-75 parts by weight of waste concrete powder, 250-550 parts by weight of styrene-acrylic emulsion, 0.35-2.6 parts by weight of dispersant, 0.7-2.6 parts by weight of defoamer, and 45-90 parts by weight of water. This patent uses waste concrete powder and inexpensive steel slag powder and fly ash as raw materials to prepare anti-carbonization coatings. Although it realizes the full utilization of waste materials and reduces the amount of chemical reagents, thereby reducing production costs, it fails to clearly reflect the performance indicators of the product in terms of anti-carbonization, so there are certain shortcomings.
[0005] There have been relevant research reports on slurries composited with organic and inorganic materials. For example, patent CN103601441B invented a two-component organic and inorganic composite anti-carbonization waterproof slurry, whose components include: cement, quartz powder, redispersible latex powder, cellulose ether, superplasticizer, hydrophobic agent, carbonization inhibitor, emulsion, water, defoamer, preservative. The carbonization inhibitor in the present invention is a mixture of calcium oxide and calcium-based montmorillonite powder, which is obtained after being modified with mineral oil. After modification, the carbonization inhibitor can effectively control the release of active ingredients, so that the coated thin layer forms a dense and uniform waterproof layer from the surface to the inside, effectively preventing water from penetrating. Although the material can provide good anti-carbonization performance, due to the wide variety of raw materials and the large amount of organic and inorganic chemical reagents used, the cost increases and the operation process is complicated.
[0006] The above methods all achieve the purpose of preventing carbonization of reinforced concrete structures by adding a coating on the concrete surface. However, from the perspective of being simpler, more convenient, and not requiring the preparation of new materials, such methods are relatively rare. Therefore, it is particularly necessary to develop an anti-carbonization solution that is easy to obtain, simple to operate, low in cost, and easy to implement. Summary of the invention
[0007] In view of this, the present invention aims to provide a method for preventing carbonization of a concrete structure, so as to solve the problem of carbonization of existing concrete structures.
[0008] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0009] A method for preventing carbonization of a concrete structure comprises the following steps:
[0010] 1) Before pouring concrete, one or more external leads are longitudinally wound or vertically fixed on the steel cage;
[0011] 2) During the concrete pouring process, the external lead is exposed to the air. The part in contact with the air can absorb the liquid in the environment to prevent the carbonization of the concrete, and transmit the liquid to the interior of the reinforced concrete structure through the track of the external lead.
[0012] Optionally, the external lead wire is one or more of cotton thread, linen thread, bamboo fiber thread, viscose fiber thread, modal fiber thread, tencel fiber thread, wool thread, and polyester fiber absorbent thread.
[0013] Optionally, the liquid for preventing concrete carbonization is prepared by mixing water and citric acid in a mass ratio of 100:(5-7).
[0014] The second object of the present invention is to provide a structure for preventing carbonization of a concrete structure, which comprises a steel cage placed in concrete and an external lead wire wound around or fixed on the steel cage; one end of the external lead wire is exposed to the air.
[0015] Optionally, the outer lead is longitudinally wound or vertically fixed on the steel cage.
[0016] Optionally, there is one or more external leads.
[0017] Optionally, the outer lead is longitudinally wound around one steel bar of the steel cage or longitudinally wound around multiple steel bars of the steel cage.
[0018] Optionally, the winding density of the external lead is 1 to 100 turns / meter.
[0019] Optionally, the density of the external lead is 0.6-1.60 g / cm3.
[0020] Optionally, the interface between the external lead and the concrete is one of a straight line, a circle, a rectangle, a U shape, and a V shape.
[0021] Compared with the prior art, the method for preventing carbonization of concrete structure according to the present invention has the following advantages:
[0022] 1. The present invention is based on the theories of "ion diffusion" and "ionization equilibrium". By winding or fixing a water-absorbent external lead on a concrete steel cage, a liquid that prevents carbonization of the concrete is transmitted to the interior of the reinforced concrete structure through the trajectory of the external lead, thereby achieving continuous moisture retention and internal acid balance inside the concrete structure, thereby achieving the purpose of reducing the transmission rate of carbon dioxide and even inhibiting the diffusion of CO2 in concrete, effectively reducing the degree of carbonization of concrete, and effectively solving the problem of reduced durability of reinforced concrete caused by carbonization, thereby extending the service life of reinforced concrete structures. The present invention is suitable for various reinforced concrete structures such as bridges, tunnels, and buildings. In addition, the present invention has a wide range of material sources, is easy to operate, and is low in cost. It can reduce the labor intensity and maintenance costs of workers during the maintenance process, and has an excellent prospect for promotion and application.
[0023] 2. The water-absorbent external lead of the present invention can also introduce concrete repair liquid into the reinforced concrete structure to repair microcracks therein, fill pores and defects in the concrete, etc., thereby improving the durability of the reinforced concrete structure and extending its service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0025] Figure 1 This is a schematic diagram of the structure of the present invention for preventing carbonization of a concrete structure;
[0026] Figure 2 This is a schematic diagram of the concrete carbonization process of the present invention;
[0027] Figure 3 This is a diagram showing the effect of preventing concrete carbonization according to Embodiment 2 of the present invention;
[0028] Figure 4 This is a diagram showing the effect of preventing concrete carbonization in Comparative Example 1 of the present invention.
[0029] Reference numerals:
[0030] 1-steel cage, 2-external lead, 3-concrete, 4-interface between external lead and concrete. DETAILED DESCRIPTION
[0031] In order to enable those skilled in the art to better understand the technical solutions and technical effects of the present invention, several embodiments are provided below. Obviously, what is described below is only an embodiment and does not limit the protection scope of the present invention.
[0032] Example 1
[0033] A method for preventing carbonization of a concrete structure comprises the following steps:
[0034] 1) Before pouring concrete, one or more external leads are longitudinally wound or vertically fixed on the steel cage;
[0035] 2) During the concrete pouring process, the external lead is exposed to the air. The part in contact with the air can absorb the liquid in the environment to prevent the carbonization of the concrete, and transmit the liquid to the interior of the reinforced concrete structure through the track of the external lead.
[0036] The above-mentioned external lead is one or more of cotton thread, linen thread, bamboo fiber thread, viscose fiber thread, modal fiber thread, tencel fiber thread, wool thread, polyester fiber water-absorbing thread. The liquid is water and citric acid mixed in a mass ratio of 100: (5-7). Based on the theory of "ion diffusion" and "ionization equilibrium", the present invention introduces a mixed solution of water and citric acid into concrete through the absorbent external lead, so that the interior of the concrete maintains a high humidity and the internal pore structure of the concrete is weakly acidic, which can effectively reduce the transmission rate of carbon dioxide and even inhibit the diffusion of CO2 in concrete, thereby effectively reducing the carbonization degree of the concrete structure, and then reducing the structural degradation problem caused by carbonization.
[0037] like Figure 1 As shown, the continuous moisture retention structure involved in the above method includes a steel cage 1 placed in concrete 3, and an external lead 2 wound or fixed on the steel cage 1; one end of the external lead 2 is exposed to the air, and can absorb liquid in the environment to prevent concrete carbonization, and transmit the liquid to the inside of the reinforced concrete structure. In this structure, the external lead 2 is longitudinally wound or vertically fixed on the steel cage 1, and the number is one or more. It can also be longitudinally wound on a steel bar of the steel cage 1 or longitudinally wound on multiple steel bars of the steel cage 1. In order to effectively absorb the liquid in the environment, the winding density of the external lead is preferably 1 to 100 turns / meter, that is, the number of external lead coils wound on a one-meter-long steel bar is 1 to 100 turns, and the density of the external lead is preferably 0.6 to 1.60 grams / cubic centimeter, that is, the mass of the external lead per cubic centimeter is 0.6 to 1.60 grams. In addition, the interface between the external lead and the concrete is one of a straight line, a circle, a rectangle, a U-shape, and a V-shape.
[0038] Example 2
[0039] The method of Example 1 of the present invention is used to prevent carbonization of concrete structure, and the carbonization effect thereof is tested. The test method is as follows:
[0040] 1) A cylindrical specimen with a diameter of 50 mm and a height of 100 mm was prepared according to the mass ratio of cement, standard sand and water of 1:3:0.5, and an external lead was pre-buried in the specimen from the lower bottom surface to the upper bottom surface, wherein a part of the external lead was exposed to the air, wherein the winding density of the external lead was 1 turn / m, the density of the external lead was 1.14 g / cm3, and the interface form between the external lead and the concrete was circular;
[0041] 2) After 24 hours of demoulding, the cylindrical specimen with embedded external leads was cured in a standard curing room for 3 days;
[0042] 3) The outer lead of the cylindrical specimen is connected to the external liquid (water and citric acid mixed in a mass ratio of 100:6). After that, the specimen is placed in a carbonization box for carbonization and curing for 28 days. The carbonization conditions are temperature 20°C, humidity 75%, CO2 concentration 20%. The carbonization process is as follows: Figure 2 As shown;
[0043] 4) After carbonization, take cylindrical surfaces at different heights and titrate with phenolphthalein to test the carbonization depth of the sample. Figure 3 As shown;
[0044] 5) By Figure 3 It can be seen that the carbonization depths of the samples containing external leads are 4mm, 3mm, 2mm, 3mm, 4mm, 3mm, and 2mm.
[0045] Comparative Example 1
[0046] The difference between this comparative example and Example 2 is:
[0047] 1) Prepare cylindrical specimens with a diameter of 50 mm and a height of 100 mm according to the mass ratio of cement, standard sand and water of 1:3:0.5;
[0048] 2) After demoulding for 24 hours, the cylindrical specimen was cured in a standard curing room for 3 days;
[0049] 3) After the upper and lower bottom surfaces of the cylinder are sealed with paraffin, they are placed in a carbonization box for carbonization and curing for 28 days. The carbonization conditions are temperature 20°C, humidity 75%, CO2 concentration 20%. The carbonization process is as follows: Figure 2 As shown;
[0050] 4) After carbonization, take cylindrical surfaces at different heights and titrate with phenolphthalein to test the carbonization depth of the control sample. Figure 4 As shown;
[0051] 5) By Figure 4 It can be seen that the carbonization depths of the comparison samples are 7mm, 6mm, 4mm, 10mm, 6mm, and 5mm.
[0052] Comparative Example 2
[0053] The difference between this comparative example and Example 2 is that the external liquid used in step 3) of this comparative example is water, and the rest is the same as Example 2. The carbonization depth of this comparative sample is tested, and it is found that the carbonization depth of this comparative sample is 6mm, 5mm, 3mm, 7mm, 6mm, and 4mm.
[0054] It can be seen from the carbonization depth results of Example 2, Comparative Example 1 and Comparative Example 2 that, compared with the conventional paraffin sealing and the method of introducing water alone, the present invention introduces a composite solution of water and citric acid through an external lead, which can significantly reduce the carbonization depth of concrete, indicating that the method of the present invention has a good effect in preventing carbonization of concrete.
[0055] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preventing carbonization of a concrete structure, characterized in that: The following steps are involved: 1) Before pouring concrete, one or more external leads are longitudinally wound or vertically fixed on the steel cage; 2) During the concrete pouring process, the external lead is exposed to the air. The part in contact with the air can absorb the liquid in the environment to prevent the carbonization of the concrete, and transmit the liquid to the interior of the reinforced concrete structure through the track of the external lead.
2. The method for preventing carbonization of a concrete structure according to claim 1, characterized in that: The external lead wire is one or more of cotton thread, linen thread, bamboo fiber thread, viscose fiber thread, modal fiber thread, tencel fiber thread, wool thread, and polyester fiber absorbent thread.
3. The method for preventing carbonization of a concrete structure according to claim 1, characterized in that: The liquid for preventing concrete from carbonizing is prepared by mixing water and citric acid in a mass ratio of 100:(5-7).
4. A structure for preventing carbonization of a concrete structure, characterized in that: The invention comprises a steel cage placed in concrete and an external lead wire wound or fixed on the steel cage; one end of the external lead wire is exposed to the air.
5. The continuous moisture retaining structure for preventing carbonization of concrete structure according to claim 4, characterized in that: The outer lead is longitudinally wound or vertically fixed on the steel cage.
6. The structure for preventing carbonization of a concrete structure according to claim 4, characterized in that: The external lead wires may be one or more.
7. The structure for preventing carbonization of a concrete structure according to claim 5, characterized in that: The outer lead is longitudinally wound around one steel bar of the steel cage or longitudinally wound around a plurality of steel bars of the steel cage.
8. The structure for preventing carbonization of a concrete structure according to claim 5, characterized in that: The winding density of the outer lead wire is 1 to 100 turns / meter.
9. The structure for preventing carbonization of a concrete structure according to claim 5, characterized in that: The density of the outer lead is 0.6-1.60 g / cm3.
10. The structure for preventing carbonization of a concrete structure according to claim 4, characterized in that: The interface between the external lead and the concrete is one of a straight line, a circle, a rectangle, a U shape, and a V shape.
Citation Information
Patent Citations
Concrete carbonization preventing paint
CN101693610B
Water-based transparent concrete water-proof carbonization-preventing coating and preparation method thereof
CN103333559A
Carbonization-resistant waterproof slurry
CN103601441B